The influensing of the tick-borne encephalitis virus to the process of metamorphosis of engorged larvaes and nimphs of the tick Ixodes ricinus - Yu. S. Korotkov; L. A. Burenkova (Бюллетень сибирской медицины, 2006)
In laboratory experience the conditions for development engorged larvaes (n = 2 500) and nymphs (n = 800) of Ixodes ricinus with diapause (6 h of light) are simulated. In contrast to control (diapause), the ticks with tick-borne encephalitis virus (strain EK- 328), developed under three variants; namely with diapause, with acceleration metamorphosis, and without diapause. The distinc- tions are caused by a season of the year and influence of the virus. The realization of variants carries out by stimulation or blocking of moult hormone.